COMPARATIVE STUDY BETWEEN PROPOFOL AND THIOPENTONE SODIUM IN FACILITATION OF LARYNGEAL MASK AIRWAY INSERTION - APPARAO, MEKALA; SARAIAH, RONTALA; RAJU, KOTA; ARPITHA REDDY, ADDULA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The aim of the study is to compare the conditions to facilitate the insertion of the laryngeal mask airway (LMA) with the two most commonly used agents – thiopentone and propofol, after adequate pre-medication with midazolam and fentanyl. Methods: It is prospective randomized study conducted on 70 patients of either sex, belonging to 20–60 years of age, and American Society of Anesthesiologists grades I and II who were admitted to elective minor surgeries under general anesthesia. Patients were randomly divided into 2 groups. Patients in both the groups received pre-induction doses of glycopyrrolate (0.2 mg), midazolam (0.04 mg/kg), and fentanyl (2 mcg/kg) and were induced with either propofol (2 mg/kg) or thiopentone (5 mg/kg), to facilitate insertion of LMA. The parameters were studied and were conditions for insertion, time taken, hemodynamic changes during insertion of LMA, and immediately thereafter. Results: Conditions for insertion, ease of insertion was significantly greater in propofol group when compared to thiopentone group. The difference was statistically significant (p<0.05). The heart rate, systolic blood pressure, and diastolic blood pressure were compared between the 2 groups. It was observed that there was a fall in all these parameters in both groups, but it was more pronounced in the propofol group. Although this was statistically extremely significant (p<0.001), it was not clinically significant. Conclusion: It was concluded that, due to better ease of insertion, lesser time taken for insertion, and better recovery profiles observed with propofol, it seemed to be slightly superior to thiopentone as an induction agent for insertion of the LMA.